Analysis of Calculation of Cost of Production Based on Orders by the Full Costing Method on the CV. Citra Karya Media - Novelia Asita Mranani; Siwidyah Desi Lastianti; Yanna Eka Pratiwi (Faculty of Economics, Merdeka University Surabaya, Indonesia, 2019)
This study aims to analyze the calculation of production costs in determining product prices by CV. Citra Karya Media with the full costing method. The problem in this study is